Understanding sleep-wake mechanisms and drug discovery. (3rd July 2017) - Equihua-Benítez, Ana Clementina; Guzmán-Vásquez, Khalil; Drucker-Colín, René
ABSTRACT: Introduction : Although not discernible at first glance, sleep is a highly active and regulated brain state. Although we spend practically one third of our lifetimes in this stage, its importance is often taken for granted. Sleep loss can lead to disease, error and economic loss. Our understanding of how sleep is achieved has greatly advanced in recent years, and with that, the management of sleep disorders has improved. There is still room for improvement and recently many new compounds have reached clinical trials with a few being approved for commercial use. Areas covered : In this review, the authors make the case of sleep disorders as a matter of public health. The mechanisms of sleep transition are discussed emphasizing the wake and sleep promoting interaction of different brain regions. Finally, advances in pharmacotherapy are examined in the context of chronic insomnia and narcolepsy. Expert opinion : The orexinergic system is an example of a breakthrough in sleep medicine that has catalyzed drug development. Nevertheless, sleep is a topic still with many unanswered questions. That being said, the melanin-concentrating hormone system is becoming increasingly relevant and we speculate it will be the next target of sleep medication.